(untitled) (Mustansiria Dental Journal, 2018)
Although favorable long-term results of implant therapy have been reported, complications as infections of peri-implant mucosa (Peri-implant mucositis) and deeper implant supporting tissues (Peri-implantitis) had been repeatedly reported. Studies regarding prevalence of peri-implant mucositis and peri-implantitis in our community are very rare because of the recent introduction of this new area of dental treatment to our country. So the aim of this study is to take an idea about the real state of implant dentistry in our community and to enrich the very poor base line data that available on this dental practice in Iraq. Sample of this research composed of 24 patients (13 Females &11 Males). Their age range was (20-60 years). All of them had worn more than two implants for at least two years. Results of this research revealed that percentage of females’ worn implants (54.17%) was greater than males (45.83%). Greater percentage of patients had worn implant for two years (45.83%) in comparison with other durations. Radiographic results revealed that there is no bone loss in most cases (66.67%) and in the remaining percentage horizontal bone loss(20.83%) was greater than vertical(12.5%). Clinical examination showed non significant differences between females and males for both Plaque Index (PLI) & Bleeding On Probing (BOP) scores.